The Emergence of the Category of Turkish Classical Music and Rauf Yekta:Turkish Classical Music Versus Other Musics - Ayas, Onur Gunes (ISTANBUL UNIV, 2024)
This study examines how Rauf Yekta positioned Turkish classical music in contrast to other musical genres while formulating it as a distinct category. Elements of traditional Ottoman music that appealed to elite tastes were associated with the category of classical music for the first time at the end of the nineteenth century. The category of Turkish classical music was established to preserve the status and demarcate the boundaries of Ottoman-Turkish high music culture, whose place in hierarchies of taste had become blurred and which experienced a crisis of legitimacy during the transition from the Ottoman Empire to Republican T & uuml;rkiye. This reformulation was also part of the efforts to incorporate it into the discourses of national music. This study argues that Rauf Yekta played a pivotal role in constructing the category of Turkish classical music, delineating its boundaries, and developing arguments to establish its superiority over other music genres. Accordingly, the primary texts written by Rauf Yekta, spanning from the late 1800s to his death in 1935, as well as the interviews with him, were analyzed from the perspective of music sociology within the framework of the late Ottoman and early Republican discussions. It is concluded that the position of Turkish classical music throughout Republican T & uuml;rkiye's history has been significantly shaped by Rauf Yekta's intellectual framework.
Keywords: Turkish classical music; Ottoman music; sociology of music; sociology of taste; history of Turkish music; Area Studies; History